قاعدة اقتضاء النهي الفساد و البطلان عند المذاهب الأربعة و تطبيقاتها في المناكحات - S Suranto; Imron Rosyadi; Muinudinillah Basri (Profetika: Jurnal Studi Islam, 2020)
The title of this research is the rule of “Iqtidho’u annahyi alfasad wa albutlan” in the perspective of four ideology of thought and their application in marriage, a thesis proposed to meet one of the requirements to achieve a master’s degree of fiqh and the ushul. Written by Suratno, NIM: O200170020, under the guidance of Dr. Imron Rosyadi and Dr. Muinudinillah Basri.This research is motivated by the curiosity of the law of marriage of a pregnant adulter to cover up her shame and family disgrace, which sometimes occurs in the community, while the Prophet Muhammad “peace be upon him” has forbidden men to marry a pregnant woman until she gives birth.And many other forbidden marriages that occur in the community. The formulation of the problems of this research are: 1) What are the opinions of the four ideology of thought towards the rule of “iqtidhou annahyi alfasad wal butlan”? 2) How is the application of this rule in prohibited marriages, such as marriages of men with adulterers who are pregnant, mut’ah marriages, marriages of men who have been proposed by other men, marriages in ihrom conditions, syigor marriages, bid’iy marriages, marriages without marriages proxy, marriage without witnesses, marriage by combining women who still have mahrom relations. This research was conducted by the literature review method, collecting and studying various references, especially from the four ideology of thought, then conducting in-depth analysis. The conclusions of this study are 1) the four ideology of thought differ on the the rule of “iqtidhou annahyi alfasad wal butlan” in some circumstances annahyu, and have the same view of this Qoidah in several circumstances annahyu. 2) In applying this rule in the case of marriage, they agree on its validity or sleaze in some marital matters, but also differing opinions in several other issues. Usually, their opinions on the issue of marriage are in line with their opinions on the issue of the rule of ushul, but sometimes they don’t.